Queueing networks with infinite servers in each node (an application in logistics) - Ferreira, Manuel Alberto M. (2013)
After a report of results about queueing systems with infinite servers, namely considering its busy period, we intend to build a model, using networks of queues with infinite servers in each node, to study a two echelons repair system of a fleet of aircraft,of shipping or of trucking. The customers are the failures. And its service time is the time that goes from the instant at which they occur till the one at which they are completely repaired. The failures repairs occur in a base or in a remote station. The whole failures detected in the base are repaired there. Some of the failures detected in the station are repaired in the base, and the others in the station. The results referred above, about the infinite servers queues busy period, allow the determination of the two echelons repair system performance measures. In this application we work over models of Carrillo (1991) and Ferreira (1996) that we improve and complete. We will illustrate the theory with a very simple and short numerical example.